2021
DOI: 10.3390/v13091800
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Codon Usage in Coronaviruses Is Mainly Driven by Mutational Bias and Selective Constraints on CpG Dinucleotide

Abstract: The Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the third human-emerged virus of the 21st century from the Coronaviridae family, causing the ongoing coronavirus disease 2019 (COVID-19) pandemic. Due to the high zoonotic potential of coronaviruses, it is critical to unravel their evolutionary history of host species breadth, host-switch potential, adaptation and emergence, to identify viruses posing a pandemic risk in humans. We present here a comprehensive analysis of the composition and co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 108 publications
3
6
0
Order By: Relevance
“…Indeed, the bias against C and G nucleotides observed in third codon-positions, which appeared more marked for PangSar and SCoV2rC ( Table 2 ), was also detected by comparing the frequencies of dinucleotides ( Table 3 ) or four-fold degenerate codons (amino-acids A, G, P, T, and V in Table 4 ). In agreement with several previous studies, my results confirmed therefore that mutational bias is the main force shaping codon usage in sarbecoviruses ( Tort et al, 2020 , Daron and Bravo, 2021 , Simmonds and Ansari, 2021 ). Importantly, the bias in favour of C=>U transitions (over U=>C transitions) has been observed in a wide range of mammalian RNA viruses ( Simmonds and Ansari 2021 ), indicating that it is the result of an asymmetrical mechanism shared by all RNA viruses infecting mammals.…”
Section: Viral Rna Replication In Different Hosts Is the Main Evoluti...supporting
confidence: 93%
See 2 more Smart Citations
“…Indeed, the bias against C and G nucleotides observed in third codon-positions, which appeared more marked for PangSar and SCoV2rC ( Table 2 ), was also detected by comparing the frequencies of dinucleotides ( Table 3 ) or four-fold degenerate codons (amino-acids A, G, P, T, and V in Table 4 ). In agreement with several previous studies, my results confirmed therefore that mutational bias is the main force shaping codon usage in sarbecoviruses ( Tort et al, 2020 , Daron and Bravo, 2021 , Simmonds and Ansari, 2021 ). Importantly, the bias in favour of C=>U transitions (over U=>C transitions) has been observed in a wide range of mammalian RNA viruses ( Simmonds and Ansari 2021 ), indicating that it is the result of an asymmetrical mechanism shared by all RNA viruses infecting mammals.…”
Section: Viral Rna Replication In Different Hosts Is the Main Evoluti...supporting
confidence: 93%
“…Several mechanisms have been proposed to account for the cytosine deficiency in the genome of sarbecoviruses, such as cytosine deamination resulting from the action of the host APOBEC3 system ( Milewska et al 2018 ), methylation of CpG dinucleotides (Xia 2020), or the limited availability of cytidine triphosphate (CTP), which is used not only for the viral RNA genome synthesis but also for the synthesis of the virus envelope, as well as translation and glycosylation of viral proteins (Ou et al 2021). My results indicated that CG dinucleotides are less frequent than other dinucleotides at both P23 and P31 sites, confirming therefore the selection against CpG dinucleotide discussed in previous studies ( Daron & Bravo, 2021 ). However, this is obviously not the main mechanism explaining the differences between the eight SNC groups.…”
Section: Viral Rna Replication In Different Hosts Is the Main Evoluti...supporting
confidence: 86%
See 1 more Smart Citation
“…In viruses, CUB can be strongly influenced by overall G+C content [25,42,44,98]. This is indeed the case in poxviruses, as we found an extremely strong correlation between variation along the first component of the PCA (PC1) and the variation in G+C content in the third codon position (GC3) (Fig.…”
Section: Codon Usage Bias Is Strongly Influenced By Genomic G+c Contentsupporting
confidence: 67%
“…Only 14% and 17% of cytosine and guanine SNVs are, respectively, C > G and G > C transversions. This may reflect the CpG avoidance that has been described for SARS-CoV-2 and other coronaviruses [ 45 , 46 ]. This CpG dinucleotide suppression is thought to be due to the fact that it is evading the zinc-finger antiviral protein (ZAP) that specifically binds CpG dinucleotides in ssRNA and causes its degradation [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 90%